Efektivitas Suplementasi Semanggi Merah Dan Minyak Ikan Terhadap Kualitas Hidup Wanita Pascamenopause - Tengku Sri Wahyuni; Safrina Safrina; Sri Hernawati Sirait (Window of Health : Jurnal Kesehatan, 2022)
Menopause causes major changes in reproductive and non-reproductive tissues. Estimating that 75% of postmenopausal women experience severe complaints. Changes during the menopausal transition risk-reducing women's quality of life. Supplementation of red clover and fish oil are some supplements that are used to overcome various menopause complaints. There are still few studies that compare the effectiveness of the two to improve quality of life. This study was to compare red clover with fish oil supplementation to improve the QOL in postmenopausal women. The quasi-experimental study with a nonequivalent control group design of 60 postmenopausal women was conducted. Participants were selected by consecutive sampling and equally divided into two groups. Each group was given red clover 400 mg once a day and fish oil supplementation 1000 mg (contains omega-3 marine triglycerides 300 mg as Eicosapentaenoic Acid (EPA) 180 mg and Docosahexaenoic Acid (DHA) 120 mg) once a day for twelve weeks. Quality of life was assessed using WHOQOL-BREF and postmenopausal complaints using a menopause rating scale questionnaire. The data were analyzed by Mann-Whitney U test, Wilcoxon Signed Rank test, and paired sample t-test. The mean (standard deviation) scores of the menopause rating scale (MRS) in the fish oil group were lower (2.10 [3.30]) than in the red clover group (3.97 [5.15]); p = 0.100. There were differences in QOL scores in the domain of psychical health (p=0.006), psychological (0.005), social relationships (0.010), and environment (0.010) in the fish oil group. In contrast, in the red clover group, differences were found in the domain of psychological (p=0.020), social relationships (0.022), and environment (0.002). There was no difference between the two groups.Fish oil supplementation was as effective as red clover to improve quality of life. Fish oil and red clover supplementation should be given to postmenopausal women with menopause complaints.